2005
DOI: 10.1093/hmg/ddi256
|View full text |Cite
|
Sign up to set email alerts
|

CCM1 and CCM2 protein interactions in cell signaling: implications for cerebral cavernous malformations pathogenesis

Abstract: Cerebral cavernous malformations (CCMs) are sporadically acquired or inherited vascular lesions of the central nervous system consisting of clusters of dilated thin-walled blood vessels that predispose individuals to seizures and stroke. Familial CCM is caused by mutations in KRIT1 (CCM1) or in malcavernin (CCM2), the murine ortholog of which was concurrently characterized as osmosensing scaffold for MEKK3 (OSM). The roles of the CCM proteins in the pathogenesis of the disorder remain largely unknown. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
282
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(291 citation statements)
references
References 29 publications
7
282
0
2
Order By: Relevance
“…CCM2 Localizes Smurf1 by Binding the HECT Domain-We have shown that CCM2 regulates localization of the MEKK3-MKK3-p38 signaling module and localization of KRIT1 (1,13). Therefore, we hypothesized that CCM2 regulates Smurf1 localization.…”
Section: Ccm2 Is Not a Smurf1 Substrate Nor Does It Affect Smurf1mentioning
confidence: 97%
“…CCM2 Localizes Smurf1 by Binding the HECT Domain-We have shown that CCM2 regulates localization of the MEKK3-MKK3-p38 signaling module and localization of KRIT1 (1,13). Therefore, we hypothesized that CCM2 regulates Smurf1 localization.…”
Section: Ccm2 Is Not a Smurf1 Substrate Nor Does It Affect Smurf1mentioning
confidence: 97%
“…In humans, the genetic disorder CCM is characterized by vascular lesions localized to the CNS. The most common form of CCM (CCM1) is due to mutations in KRIT1 (35), which interacts with CCM2 (the gene mutated in CCM2), with both proteins hypothesized to play a role in endothelial cell signal transduction via the p38 MAPK pathway (36). Because PAK2 has been implicated in the activation of the p38 signaling cascade (37), defects in the Pak2/␤-pix pathway could account for additional, unexplained cases of CCM or could function as modifier genes in these disorders or in clinical settings such as CNS hemorrhage in premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been established that the three CCM proteins can form a complex. [39][40][41] How and whether disruption of this complex of CCM1, CCM2, and CCM3 is involved in the pathogenesis of CCM is still highly unknown.…”
Section: 32mentioning
confidence: 99%